KEABSAHAN SERANGAN DRONE OLEH RUSIA TERHADAP UKRAINA DI WILAYAH KURSK BERDASARKAN PRINSIP JUS AD BELLUM - Kandi Kirana Larasati; Fajrin, Fera Wulandari; Tombi, Johan Tri Noval Hendrian (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2025)
States are legal subjects with international personalities subject to the provisions of international law. However, differences in jurisdiction and interests between states can lead to conflicts that risk disrupting world peace. International Humanitarian Law plays a role in reducing the suffering caused by war by regulating the law in armed conflict, including the Jus Ad Bellum Principle that determines the legality of the use of military force. This legal research is conducted through a statute approach, conceptual approach and case approach. The purpose of this research is to analyze the rules of the use of weapons based on the Jus Ad Bellum Principle and Russia's legal basis in attacking Ukraine in Kursk from the perspective of International Humanitarian Law.